2003
DOI: 10.1001/archpedi.157.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Asthma in Inner-city Elementary Schoolchildren

Abstract: Access to SBHCs was associated with a reduction in the rate of hospitalization and a gain of 3 days of school for schoolchildren who have asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 16 publications
2
29
1
Order By: Relevance
“…Students who are receiving assistance related to their emotional and behavioral well-being may experience improvements that are directly related to their ability to succeed academically in the classroom (e.g., improved ability to focus, increased positive affect). Our finding of differential effects for subgroups of SBHC users (medical vs. mental health) is also consistent with other studies [7,12], and lends support to the strategy of testing subgroup differences as a promising model for further SBHC research. For example, Geierstanger and Amaral [15] suggest that significant findings for attendance are often revealed in subgroup analyses, especially among groups with chronic conditions associated with high absenteeism such as asthma, depression and attention deficit hyperactivity disorder.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Students who are receiving assistance related to their emotional and behavioral well-being may experience improvements that are directly related to their ability to succeed academically in the classroom (e.g., improved ability to focus, increased positive affect). Our finding of differential effects for subgroups of SBHC users (medical vs. mental health) is also consistent with other studies [7,12], and lends support to the strategy of testing subgroup differences as a promising model for further SBHC research. For example, Geierstanger and Amaral [15] suggest that significant findings for attendance are often revealed in subgroup analyses, especially among groups with chronic conditions associated with high absenteeism such as asthma, depression and attention deficit hyperactivity disorder.…”
Section: Discussionsupporting
confidence: 90%
“…The positive impact of SBHC use on important public health-related outcomes is well documented and is an important justification for the continued place of SBHCs within the public health system [3,[11][12][13][14]. However, the increased political demand for academic accountability in school health services particularly heightens the need for well-controlled, longitudinal studies examining the specific academic impact of SBHC use [15].…”
Section: Sbhc Impact On Academic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that the prevalence of asthma among elementary school-aged children ranges from 10 to 20%. 18,19,33,34 Therefore, the predictive values of the procedures described are likely to be lower in practice than seen in this study population. Furthermore, when these procedures are used in a community setting, children will most likely be referred to their primary care practitioner, who may be less apt to make a diagnosis of asthma than were the specialists participating in this study.…”
Section: E464mentioning
confidence: 78%
“…School SES was based on student free or reduced-price lunch eligibility, a commonly used measure of SES in school-based research. [39][40][41] The dependent variable was tested for normality using the Shapiro-Wilk Test of Normality and was normally distributed. Two-tailed P < .05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%